Trust in cyberspace - Schneider, Fred B.; National Research Council (U.S.). Committee on Information Systems Trustworthiness (Washington, D.C. : National Academy Press, 1999)
"This book provides an assessment of the current state of the art for building trustworthy networked information systems. It proposes directions for research in computer and network security, software technology, and system architecture. In addition, it assesses current technical and market trends in order to better inform public policy as to where progress is likely and where incentives could help."--Jacket
Introduction -- Public telephone network and Internet trustworthiness -- Software for networked information systems -- Reinventing security -- Trustworthy systems from untrustworthy components -- The economic and public policy context -- Conclusions and research recommendations.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
English.
Keywords: Computer networks -- Security measures; Telecommunication policy -- United States; Internet -- Security measures; Computer security; Telecommunication; Computer Security; Telecommunications; Internet; Public Policy; Réseaux d'ordinateurs -- Sécurité -- Mesures; Télécommunications -- Politique gouvernementale -- États-Unis.; Internet -- Sécurité -- Mesures; Sécurité informatique; Télécommunications.; telecommunications; BUSINESS & ECONOMICS -- Industries -- Media & Communications; TECHNOLOGY & ENGINEERING -- Telecommunications; Telecommunication; Computer security; Computer networks -- Security measures; Internet -- Security measures; Telecommunication policy; United States; Verteiltes System; Sicherheit; Telekommunikationspolitik; Internet; USA